The cardiometabolic benefits of okra-based treatment in prediabetes and diabetes: a systematic review and meta-analysis of randomized controlled trials - Bahari, Hossein; Shahraki Jazinaki, Mostafa; Rahnama, Iman; Aghakhani, Ladan; Amini, Mohammad Reza; Malekahmadi, Mahsa (Frontiers in Nutrition, 2024)
BackgroundThis systematic review and meta-analysis examine the effects of okra consumption on cardiometabolic risk factors in individuals with prediabetes and diabetes. Okra is a widely consumed vegetable with potential health benefits, and understanding its impact on metabolic parameters in these populations is important.MethodsA comprehensive search of the literature was conducted up to May 2024 in PubMed/Medline, Scopus, and Web of Science to find relevant randomized clinical trials (RCTs) by using following keyword: (“okra” OR “okras” OR “abelmoschus esculentus”) AND (“intervention” OR “controlled trial” OR “randomized” OR “randomized” OR “randomly” OR “clinical trial” OR “trial” OR “randomized controlled trial” OR “randomized clinical trial” OR “RCT” OR “blinded” OR “placebo” OR “Cross-Over” OR “parallel”). The selected trials were subjected to heterogeneity tests using the I2 statistic. Random effects models were examined based on the heterogeneity tests, and the pooled data were calculated as weighted mean differences (WMD) with a 95% confidence interval (CI). In this meta-analysis, all the analyses were performed by using the STATA version 17 software.ResultsOf the 1,339 papers, nine eligible RCTs were included in the present meta-analysis. Our findings indicated that okra consumption significantly reduced total cholesterol (TC) levels (WMD: −14.40 mg/dL; (95% CI: −20.94 to −7.86); p < 0.001), low-density lipoprotein (LDL) (WMD: −7.90 mg/dL; (95% CI: −13.30 to −2.48); p = 0.004), fasting blood glucose (FBG) (WMD: −39.58 mg/dL; (95% CI: −61.60 to −17.56); p < 0.001), and hemoglobin A1C (HbA1c) (WMD: −0.46 mg/dL; (95% CI: −0.79 to −0.13); p = 0.005). Overall effect size showed that okra intake failed to change triglycerides (TG), high-density lipoprotein (HDL), Insulin, homeostatic model assessment for insulin resistance (HOMA-IR), systolic blood pressure (SBP), diastolic blood pressure (DBP), body weight, and body Mass Index (BMI) significantly.ConclusionOkra decreased TC, LDL, FBG, and HbA1c levels in the intervention compared to the control group. A dose ≤3,000 mg/day caused a significant decrease in TG, TC, LDL, HbA1c, and a significant increase in HDL. More study is needed to determine the optimum dose and duration of intervention.